The First Women Bank-Why and for Whom? (The Pakistan Development Review, 1991)
The First Women Bank which commenced operations in December 1989, has over a period of one year, set up 10 branches in the big cities of the country. The name of the bank suggested that it would function on the same lines as the Grameen Bank of Bangladesh. It was widely believed that the Bank was meant to assist the very poor women in their economic uplift. However, with the exception of two branches (one in Gurumander, Karachi and the second in Sukkur), the branches of the bank have been set up in posh localities like Defence, Cantonment, Blue Area and Mall Roads. The expensive location and the expensive set-up of these banks has created the image that these banks are meant to cater for the rich, elite women, rather than the poor deserving women. The very poor earning women in low-income localities are totally unaware of this bank's existence because it has not been advertised to them through audio or video media. However they envied poor women in India who benefited from the credit schemes for women, as shown on Indian television.l This paper attempts to look into the factors behind the establishment of the bank and its working strategy, to clarify, to whatever extent possible, the confusions or contradictions associated with this bank. Section II puts forward the various factors underlying the establishment of a separate bank for women in Pakistan. Section III describes the operational strategy of the bank with special focus on the nature of clientele and credit services of the bank. Section IV puts forward the conclusions and Section V gives some policy recommendations. The paper is based on the published material made available by the bank i.e. the brochure of the bank (the first annual statement of the bank had not been published at the time of writing this paper), informal discussions with the bank staff, and personal observations of the author during the working hours of the bank.